Effective Strategic Management in Improving the Quality of Senior Secondary Education Units - Fany Oktavia; Ratih Cahyani; Sodiran; Lilis Suwandari (Journal of Educational Management Research, 2025)
This study aims to analyze effective strategic management practices for enhancing the quality of senior secondary education units in Indonesia. The role of secondary education is crucial as it serves as a bridge between basic education and either higher education or direct entry into the workforce. However, the sector faces persistent and multi-dimensional challenges, including disparities in access and quality across regions, inequitable distribution of qualified teachers, limited financial resources, and the insufficient integration of school programs with market demands. Employing a qualitative literature review and document analysis methodology, this study synthesizes findings from national education policies, empirical studies, and international best practices. The discussion encompasses visionary educational planning, comprehensive curriculum management, human resource development, facilities and infrastructure optimization, financial stewardship, stakeholder collaboration, and the integration of information technology. The findings indicate that a holistic, adaptive, and stakeholder-engaged approach to management—grounded in data-driven decision-making and continuous improvement—is fundamental to fostering sustainable and high-quality senior secondary education. The paper concludes with recommendations for strengthening school management systems through professional development, participatory leadership, and technological innovation.